Cervical spinal cord volume loss is related to clinical disability progression in multiple sclerosis. Issue 4 (27th June 2014) - Lukas, Carsten; Knol, Dirk L; Sombekke, Madeleine H; Bellenberg, Barbara; Hahn, Horst K; Popescu, Veronica; Weier, Katrin; Radue, Ernst W; Gass, Achim; Kappos, Ludwig; Naegelin, Yvonne; Uitdehaag, Bernard M J; et al.
Abstract : Objective: To examine the temporal evolution of spinal cord (SC) atrophy in multiple sclerosis (MS), and its association with clinical progression in a large MS cohort. Methods: A total of 352 patients from two centres with MS (relapsing remitting MS (RRMS): 256, secondary progressive MS (SPMS): 73, primary progressive MS (PPMS): 23) were included. Clinical and MRI parameters were obtained at baseline, after 12 months and 24 months of follow-up. In addition to conventional brain and SC MRI parameters, the annualised percentage brain volume change and the annualised percentage upper cervical cord cross-sectional area change (aUCCA) were quantified. Main outcome measure was disease progression, defined by expanded disability status scale increase after 24 months. Results: UCCA was lower in SPMS and PPMS compared with RRMS for all time points. aUCCA over 24 months was highest in patients with SPMS (−2.2% per year) and was significantly higher in patients with disease progression (−2.3% per year) than in stable patients (−1.2% per year; p=0.003), while annualised percentage brain volume change did not differ between subtypes (RRMS: −0.42% per year; SPMS −0.6% per year; PPMS: −0.46% per year) nor between progressive and stable patients (p=0.055). Baseline UCCA and aUCCA over 24 months were found to be relevant contributors of expanded disability status scale at month-24, while baseline UCCA as well as number of SC segments involved by lesions at baseline but not aUCCA were relevant contributors of disease progression. Conclusions: SC MRI parameters including baseline UCCA and SC lesions were significant MRI predictors of disease progression. Progressive 24-month upper SC atrophy occurred in all MS subtypes, and was faster in patients exhibiting disease progression at month-24.